1992
DOI: 10.1530/acta.0.1270403
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal hormones in human follicular fluid

Abstract: hormones in human follicular fluid. Acta Endocrinol 1992;127:403-6. ISSN 0001-5598Considerable evidence indicates that adrenal hormones may affect gonadal function. To assess the role of some adrenal hormones in human follicular fluid and their relationship with the ability of the oocyte to be fertilized and then to cleave in vitro, cortisol and dehydroepiandrosterone sulfate were measured in follicular fluid obtained at the time of oocyte recovery for in vitro fertilization from cycles stimulated by clomiphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…However, the latter of these studies found the total and free intrafollicular cortisol concentrations to be up to 12% higher in FF samples from patients that did not conceive by IVF‐ET than in those samples obtained from conception cycles (Anderson & Hornnes, 1994). Previous studies reported a similar association between modestly elevated intrafollicular cortisol concentrations and failure of oocyte fertilization (Fateh et al ., 1989; Jimena et al ., 1992), despite the fact that the intrafollicular cortisol concentration was found to be over 2‐fold higher in follicles containing mature oocytes relative to follicles containing immature oocytes (Fateh et al ., 1989). In the present study, the mean cortisol concentration in follicular fluid samples obtained from conception IVF‐ET cycles was 25% lower than that measured in follicles aspirated from nonconception cycles, consistent with the previous report by Anderson & Hornnes (1994).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the latter of these studies found the total and free intrafollicular cortisol concentrations to be up to 12% higher in FF samples from patients that did not conceive by IVF‐ET than in those samples obtained from conception cycles (Anderson & Hornnes, 1994). Previous studies reported a similar association between modestly elevated intrafollicular cortisol concentrations and failure of oocyte fertilization (Fateh et al ., 1989; Jimena et al ., 1992), despite the fact that the intrafollicular cortisol concentration was found to be over 2‐fold higher in follicles containing mature oocytes relative to follicles containing immature oocytes (Fateh et al ., 1989). In the present study, the mean cortisol concentration in follicular fluid samples obtained from conception IVF‐ET cycles was 25% lower than that measured in follicles aspirated from nonconception cycles, consistent with the previous report by Anderson & Hornnes (1994).…”
Section: Discussionsupporting
confidence: 93%
“…In our previous work, it was not possible to determine whether the clinical correlation between low ovarian 11βHSD activities and conception in IVF‐ET cycles reflects a positive role for increased ovarian exposure to cortisol in influencing subsequent embryonic development and implantation. Two prior studies have concluded that there was no association between intrafollicular cortisol concentrations and IVF‐ET outcome (Jimena et al ., 1992; Anderson & Hornnes, 1994). However, the latter of these studies found the total and free intrafollicular cortisol concentrations to be up to 12% higher in FF samples from patients that did not conceive by IVF‐ET than in those samples obtained from conception cycles (Anderson & Hornnes, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Stressors of different types [25][26][27][28] or treatments with glucocorticoids [29][30][31][32] induce apoptosis in different tissues, including testicular germ cells [33]. Fluid from follicles of women whose oocytes were not fertilized contained cortisol levels significantly higher than in the fluid from follicles containing successfully fertilized oocytes [34]. Peripheral CRH has been identified in the reproductive system, including the ovary and testis [18].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few in vitro studies are available, which show the utilization of DHEAS by granulosa cells via sulfatase for androgen and estrogen production (5,6). It is of interest, therefore, to explore further the sources of follicular DHEA and DHEAS and their roles in steroidogenesis in the setting of gonadotropin stimulation.…”
mentioning
confidence: 99%
“…There is evidence that elevated levels of DHEA and DHEAS are associated with increased cortisol (7), which can directly inhibit steroidogenesis (8). In turn, higher FF cortisol has been shown to be associated with negative IVF outcomes (6,8).…”
mentioning
confidence: 99%